Evaluating the interaction between extension educators and urban farmers in the Kansas City metropolitan area - Tanner, Caroline (Kansas State University, 2014)
With the increasing popularity of urban farming, more people are seeking resources to start their own farming/growing production in urban environments. Traditionally, county Extension educators are a key resource for beginning farmers and growers. However, urban Extension offices are often overlooked as resources in the urban farming planning process. The objectives of this study are 1) identify information urban farmers currently have, information they need, and their preferred delivery methods 2) look at the resources and information that are offered by local Extension educators in the KC metro area and 3) analyze how these two groups are communicating and what could improve to meet farmers‟ needs. This project evaluates current interaction between urban farmers and Extension educators in the Kansas City area through a two-pronged approach: a written mail-out questionnaire for urban farmers and growers in the Kansas City metropolitan area and through in-person one-on-one interviews with Extension educators that emphasize topic areas related to urban agriculture in the KC area. One hundred and nineteen farmers/growers were surveyed, and a 54.6% response rate was achieved. The majority of farmers had small, diversified farms and were relatively new to farming. Respondents were primarily older, white men that had higher education. Independently-driven sources (such as self-research, other farmers, and friends/family) were most commonly used sources among farmers. Overall, respondents ranked Extension highly in terms of information quantity, quality and as their "go to" source. Extension educators from Kansas State University, University of Missouri, and Lincoln University were interviewed one-on-one using scripted interview questions to determine topics and medias of information that are currently being offered. Production and processing information is offered the most by educators followed by distribution, equipment, and marketing information. Financial information was the least offered information topic. Extension educators use a wide variety of methods to distribute information. Most Extension educators are aware of benefits and barriers relating to urban agriculture in the KC metro area. Extension educators are addressing urban agriculture in varying degrees and the level of involvement corresponds to the Extension institution.
Keywords: Urban agriculture; University Extension; Information needs; Horticulture (0471); Sustainability (0640)